The Social Ecology of Tanayan Lanjang as the Basis for Religious Moderation in Rural Madurese Communities - Fauziah, Arinal Haq (Lembaga Penelitian dan Pengabdian Kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2025)
Modernisation, which has spread to rural areas, has shifted the social values that previously formed the basis of social and religious interaction within the community. This change is evident in the decline in the intensity of collective life, which has weakened the internalisation of moderate Islamic values at the community level. However, amid these changes, Taneyan Lanjhang remains a traditional settlement system that represents a social ecology rooted in the principles of togetherness, deliberation, and solidarity among families. This study uses a phenomenological qualitative approach with subjects consisting of religious leaders, community leaders, and family members in the Taneyan Lanjhang community in the Sampang Regency. Data was collected through participatory observation and in-depth interviews, then analysed using data reduction techniques to reveal the meaning of social and religious experiences in depth. The theoretical novelty of this research lies in the integration of the social ecology paradigm with the practice of religious moderation rooted in Madurese local wisdom. Taneyan Lanjhang is positioned as a socio-ecological entity that constructs reciprocal relationships between physical space, value systems, and religious social practices. The results of this study show that the value of ta'awun (mutual assistance) is articulated through the tradition of beretangghâ, tasamuh (tolerance) is represented in the ethics of andhap ashar, while tawazun (balance) and i'tidaal (justice) are evident in the principle of tengkayang, which regulates social harmony. This configuration shows that the Taneyan Lanjhang social ecology functions as a medium for the internalisation of moderate Islamic values that occur ecologically through the interconnectedness of humans, the social environment, and the spiritual dimension. These findings confirm the role of Taneyan Lanjhang as a model of a social ecosystem that strengthens the integration of religious values and communal cohesion while offering a new perspective in the development of studies on religious moderation based on cultural ecology.